Peran Humas Dalam Pemasaran Hotel Kawasan Anyer Pasca Tsunami Selat Sunda - Diqbal Satyanegara; Asmi Ayuning Hidayah (Sains: Jurnal Manajemen dan Bisnis, 2020)
The purpose of the research is to examine the role of PR hotels marketing in Anyer region after Sunda Strait tsunami in the end of 2018, which affect to the decline of hotels occupation rate. This research impelemented in mid years of 2019. Descriptive qualitative approach was used in this research. The population of this research are 36 hotels in Anyer region. Samples are pointed with probability sampling, therefore, 5 hotels are determined as samples representing Anyer’s hotel’s classifications, consist one five stars hotel, one four stars hotel, one three stars hotel, and three melati (jasmine) hotels. Depth interview were conduct to the managers in order to explore the role of hotel’s PR. According to the resul based on interview, PR’s roles after tusnami disasters are: communicator published positive image in mass and social media.